2004
DOI: 10.1111/j.0886-0440.2004.04100.x
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Outcome After Aorta-Radial Versus Internal Thoracic Artery-Radial Artery Grafts

Abstract: Hospital outcome after the use of the RA is similar to that of LITA with vein grafts. Univariate analysis shows less IE after direct aorta-RA anastomoses, but multivariate analysis did not show that technique of proximal RA anastomosis and number of inflow grafts are important predictors for hospital outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Berreklouw and colleagues [31], in a retrospective analysis of 512 patients, found similar in-hospital outcomes for patients who received aorta-based and ITAbased RA grafts. Al-Ruzzeh and associates [32] described the results of 600 RA patients (515 anastomosed to the aorta).…”
Section: Proximal Anastomosis and Target Vessel Characteristicsmentioning
confidence: 86%
“…Berreklouw and colleagues [31], in a retrospective analysis of 512 patients, found similar in-hospital outcomes for patients who received aorta-based and ITAbased RA grafts. Al-Ruzzeh and associates [32] described the results of 600 RA patients (515 anastomosed to the aorta).…”
Section: Proximal Anastomosis and Target Vessel Characteristicsmentioning
confidence: 86%
“…The extended conduit is long enough to reach the ascending aorta for the proximal anastomosis. It has been shown that aorta-RA grafting is followed by less perioperative cardiac events than after ITA-RA grafting [4]. This is explained by possible initial higher flow rates in grafts originating directly from the ascending aorta than in grafts originating more peripherally [8].…”
Section: Discussionmentioning
confidence: 99%
“…Composite grafts are relatively technically difficult compared with conventional aorto-coronary RA grafts. Another disadvantage of composite grafts is the reliance on single inflow (proximal left ITA) to supply all grafted territories [4].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations